Use of biologically-based complementary medicine in breast and gynecological cancer patients during systemic therapy - Loisa Drozdoff; Evelyn Klein; Marion Kiechle; Daniela Paepke (BMC, 2018)
Abstract Background Biologically-based complementary medicines (BB-CAM) including herbs and nutritional supplements are frequently taken by breast- and gynecological cancer patients undergoing systemic therapy. The aim of this study was to analyze the use of these natural CAM methods under systemic therapy. Methods From September 2014 to December 2014 and February 2017 to May 2017 all patients (n= 717) undergoing systemic therapy at the day care unit, Department of Gynecology and Obstetrics, Technical University Munich, Germany, with breast- and/or gynecological cancer were included in this survey. The self-administered 8-item questionnaire was developed to obtain information on complementary medication intake during systemic therapy. Results Among 448 respondents 74.1% reported to use complementary medication simultaneous to their systemic therapy. The most frequently applied methods during therapy were vitamins and minerals supplements (72.3%), medicinal teas (46.7%), phytotherapy (30.1%), and mistletoe (25.3%). The analysis showed that various patients-, disease- and therapy characteristics like receiving chemotherapy (p= 0.002), and younger age (younger than 60 years; p=0.017) are significantly associated with BB-CAM use. Conclusions Our data suggest that female cancer patients undergoing systemic therapy frequently use BB-CAM medicine. Therefore, it is indispensable to implement counseling and evidence-based complementary treatments into clinical routine of cancer centers. A counseling service for integrative medicine concepts and an outpatient program (ZIGG) was therefore implemented in our cancer center in 2013. Further research on the CAM intake of cancer patients is needed in order to verify drug interactions and implement specific guidelines for integrative medication concepts.